Assessment of Nurses' Knowledge toward Infection Control Measures for Hepatitis 8 Virus in Hemodialysis Units - Serwan J. Bakey, (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: to assess nurses' knowledge toward infection control measures for hepatitis a virus in hemodialysisunits and to detemine the relationship between nurses' knowledge and their demographical characteristics.%eihs:::°mg:rA5th:e;:#tt£:eoscTodbyerw9¥,C22;5];e.d°utathem°dialysisunitsofBaghdadTeachingHospha|sstatedA non-probability `tturposive" sample of (51) nurses, who were working in hemodialysis units were selectedfrom Baghdad teaching hosphals. The data were collected through the use of constructed questionnaire, whichconsists of two parts (I) Demographic data fom that consists of 10 items and (2) Nurses' knowledge form thatconsists of 6 sections contain 79 items, by means of direct interview technique with the nurses. The validity of#eo:u£Stla°#]:Tes#:t:)¥mwe:T:¥dp:::e#::gtitoth(e];)e:Poedc]:I:Sieipper¥La,n4dth:ts2:eo):abufi]t¥%aasyd:tthe,¥omoe8dDescriptive statistical analysis procedures (frequency, percentage, mean of score) and inferential statisticalanalysis procedures (person correlation coefficient, contingency coefficient) were used for the data analysis.Results: The findings of the study indicated that there is a knowledge deficit of nurses in some aspects relativeto infection control measures. No sigrificant relationship was found between nurses' knowledge and theirgender, marital status and years of experience in hospital, while a significant relationship was found betweennurses' knowledge and their age, level of education, years of experience in hemodialysis unit, sharing in trainingsessions and duration of training session that the nurses were engaged in it.